Arthur's April fool - Brown, Marc Tolon (New York : Little, Brown, 1983)
Arthur worries about remembering his magic tricks for the April Fool's Day assembly and Binky's threats to pulverize him.
3.1
K-3
K-3.
Elem. School Library Collection
Booklist
Bulletin (Center for Children's books)
Keywords: April Fools' Day -- Fiction; Magic tricks -- Fiction; Bullies -- Fiction; Animals -- Fiction; Aardvark -- Fiction; Arthur (Fictitious character : Brown) -- Fiction; April Fools' Day -- Fiction; Bullies -- Fiction; Magic -- Fiction; Aardvarks -- Fiction; Arthur (Fictional character : Brown) -- Fiction